Can a Corn-Derived Biosurfactant Improve Colour Traits of Wine? First Insight on Its Application during Winegrape Skin Maceration versus Oenological Tannins - Scalzini, Giulia (Foods, 2020)
In winemaking, oenological tannins are used to preserve wine colour by enhancing the antioxidant activity, taking part in copigmentation, and forming polymeric pigments with anthocyanins. As a novel processing aid, in this study, a biosurfactant extract was evaluated as a solubilizing and stabilizing agent of anthocyanins in red wine. The biosurfactant extract under evaluation was obtained from a fermented residual stream of the corn milling industry named corn steep liquor (CSL). Two red winegrape varieties (Vitis vinifera L. cv. Aglianico and Cabernet sauvignon) were studied for anthocyanin content and profile, and colour traits, during simulated skin maceration for 7 days at 25 °C, as well as polymerization and copigmentation at the end of maceration. A model wine solution was used as a control, which was added either with the CSL biosurfactant or with four different oenological tannins (from grape skin, grape seed, quebracho, and acacia). The results showed that CSL biosurfactant addition improved the colour properties of skin extracts by the formation of more stable compounds mainly through copigmentation interactions. These preliminary results highlighted that the effectiveness of CSL biosurfactant is variety-dependent; however, there is no significant protection of individual anthocyanin compounds as observed for delphinidin and petunidin forms using quebracho tannin.